Analysis of Static Characteristic of Hydrodynamic Bearing with Different Surface Roughnesses - Hong Guo; Lanlan Song; Shaolin Zhang; Weipei He (Jixie chuandong)
When the working surface roughness of hydrodynamic sliding bearing reaches the same magnitude （micron） as the oil film thickness， the influence of surface roughness on the characteristic parameters of bearing cannot be ignored. In order to study the influence of roughness on the static characteristics of bearing， an experimental platform is built based on M2000 friction and wear testing machine to test the sliding friction pairs of 42CrMo steel， and a Reynolds mathematical model considering the surface roughness is established and solved. According them， the characteristic parameter of bearing capacity， friction resistance and friction coefficient of oil film with different surface roughness are obtained. The results show that with the increase of the load， the friction resistance become larger and friction coefficient become smaller， with the increase of the temperature of the inlet oil under the same load， the friction resistance become smaller and friction coefficient become smaller. The larger the roughness is， the larger the friction resistance and friction coefficient are.